The Theory of the Leisure Class - Veblen, Thorstein, 1857-1929 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Theory of the Leisure Class" by Thorstein Veblen is an economic and sociological work published in 1899. Veblen introduces the concept of conspicuous leisure$1 (Bthe practice of displaying wealth and status through visible idleness rather than productivity. He traces how the wealthy classes throughout history have showcased their power by abstaining from labor, employing servants, and consuming time unproductively. The work examines how this behavior validates inequality and shapes social hierarchies across stratified societies. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Conspicuous_leisure
Release date is 1997-03-01
Produced by David Reed, and David Widger
Keywords: Sociology; Leisure class